2006
DOI: 10.1002/bmc.718
|View full text |Cite
|
Sign up to set email alerts
|

Determination of polymethoxylated flavones in peels of selected Jamaican and Mexican citrus (Citrus spp.) cultivars by high‐performance liquid chromatography

Abstract: The concentrations of the polymethoxylated flavones (PMFs) in peels of selected citrus cultivars grown in Jamaica and Mexico were determined. The PMFs were extracted from sun-dried citrus peels with reagent-grade methanol. Analyses were carried out by reverse-phase HPLC and UV detection. The column used was a C(18) 5 microm (150 x 4.6 mm) Discovery column. Elution was in the gradient mode, using a ternary mobile phase. The results showed that all the citrus cultivars used contained at least three of the six ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
3
22
1
Order By: Relevance
“…Early studies have shown that citromitin exists in some species of citrus (5, 6), but to our knowledge little biological effect of the compound has been demonstrated. On the other hand, there are a number of reports concerning a variety of biological effects of tangeretin and nobiletin, especially nobiletin, in addition to the concentrations of polymethoxy flavones in various species of citrus (10,11). For instances, direct and indirect evidences have been provided for anti-cancer effects (12)(13)(14)(15)(16)(17)(18)(19)(20), anti-inflammatory effects (21)(22)(23)(24), inhibition of NO production (25,26), enhancement of differentiation and lipolysis of adipocytes (27), prevention of cartilage destruction (28), improvement of memory impairment (29) and neurodegradation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have shown that citromitin exists in some species of citrus (5, 6), but to our knowledge little biological effect of the compound has been demonstrated. On the other hand, there are a number of reports concerning a variety of biological effects of tangeretin and nobiletin, especially nobiletin, in addition to the concentrations of polymethoxy flavones in various species of citrus (10,11). For instances, direct and indirect evidences have been provided for anti-cancer effects (12)(13)(14)(15)(16)(17)(18)(19)(20), anti-inflammatory effects (21)(22)(23)(24), inhibition of NO production (25,26), enhancement of differentiation and lipolysis of adipocytes (27), prevention of cartilage destruction (28), improvement of memory impairment (29) and neurodegradation (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent paper, in which the juice samples were prepared by isolating of the endocarp, demonstrated that they are virtually absent in juice. Therefore, it is probable that in previous reports they were found as a result of sample preparation procedures and derived from the essential oils fraction of the peel [30,73].…”
Section: Orangementioning
confidence: 99%
“…(JAI Inc., Japan) eluted by methanol-water (60:40, v/v). (Green et al, 2006). The flow-rate was 1 ml/min.…”
Section: Separation Of Crude Pfmsmentioning
confidence: 99%
“…Amongst them, polymethoxyflavones (PMFs) show chemopreventive potential in antimutagenic and antitumor properties (Li, Lambros, Wang, Goodnow, & Ho, 2007;Li et al, 2009aLi et al, , 2009bWalle, 2007). Various Citrus species present different composition of PMFs (Green, Wheatley, Osagie, St. A. Morrison, & Asemota, 2006;Hirata et al, 2009;Li, Pan, et al, 2007;Mizuno, Iinuma, Ohara, Tanaka, & Iwamasa, 1991). Ponkan, the fruit of Citrus reticulata Blanco cv.…”
Section: Introductionmentioning
confidence: 98%